Chimeric posterior tibial artery flap: clinical application in oral and maxillofacial reconstruction. Issue 8 (August 2020) - Mashrah, M.A.; Mai, L.; Wan, Q.; Pan, C.
Abstract: The objective was to describe the utility of the chimeric posterior tibial artery flap (CPTAF) in the restoration of compound defects in the oral and maxillofacial region. Patients who underwent head and neck reconstruction using a CPTAF between February 2018 and February 2019 were included. Special consideration was given to the distribution of septocutaneous perforators (SPs), indications, flap survival, and complications. Nine patients were included. All flaps survived. One patient developed a surgical site infection, which was managed conservatively. The CPTAF was raised as a bipaddle skin flap without muscle ( n  = 1), with the gastrocnemius muscle ( n  = 6), or with the soleus muscle ( n  = 2). The number of SPs ranged from three to five (mean 4 ± 0.8). The SPs were mostly located between 4 cm and 20 cm proximal to the medial malleolus (mean 9.5 ± 3.8 cm). The skin paddle was used to reconstruct skin or mucosal defects, whereas the muscle part was used to fill the dead space ( n  = 7) or to support the orbital contents ( n  = 1). The donor site healed with no associated functional complications. The CPTAF is a good option for the restoration of composite tissue defects in the head and neck region. It offers flexibility during flap inset and provides the appropriate bulk to repair defects in multiple planes.